PENDEKATAN HERMENEUTIK DALAM STUDI ISLAM - Abdulloh Labib (STIS MIFTAHUL ULUM LUMAJANG PRESS (STISMU PRESS), 2022)
This article aims to explain and provide insight that hermeneutics is one of the approach or theory that can help someone to understand the text of the scriptures. the presence of hermeneutics is also very influential on Islamic studies which basically have the nuances of